Dynamical Study of a Vector Host Epidemic Model With Non-Monotone Incidence. Issue 1 (2nd January 2021) - Raut, Seem A; Janardhan, Sujatha; Khekare, Ganesh
Abstract: Epidemics of vector borne disease studied in this paper when disease incidence rate is non- monotone. Non monotonic behaviors of infected hosts as well as infected vectors are studied for influence of increase in disease on susceptible host population and effect of repellents and insecticides on vectors, respectively. Suitable Liapunov functions are constructed to discuss the global asymptotic stabilities at the equilibrium points. Results are verified by conducting numerical simulation. Mechanism of disease spread by vectors and hosts during the epidemic can be better understood with the help of this model.